2016
DOI: 10.1159/000443983
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss Associated with Platinum-Based Chemotherapy in Patients with Advanced Lung Cancer

Abstract: Background: We examined whether the weight loss that occurs with platinum-based chemotherapy in lung cancer patients is associated with chemotherapy side effects, treatment completion rates and therapeutic effect. Methods: We retrospectively reviewed charts of advanced lung cancer patients treated with ≥2 cycles of platinum-based chemotherapy. Patients were divided into 2 groups based on ≥5 or <5% weight loss. Relationships between weight loss and other variables were investigated. Results: Among 114 patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Amongst UWL patients, the most common prescribed medications were statins, calcium channel blockers and calcium, which were prescribed for treatment of common co-morbidities including dyslipidemia and hypertension. The prescription of chemotherapy was significantly higher in older patients with UWL, similar to previous studies [ 46 , 47 ]. Chemotherapy contributes to changes in taste such as altered structure of taste buds and number of taste cell receptors, and detection of drug sensation via saliva [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 90%
“…Amongst UWL patients, the most common prescribed medications were statins, calcium channel blockers and calcium, which were prescribed for treatment of common co-morbidities including dyslipidemia and hypertension. The prescription of chemotherapy was significantly higher in older patients with UWL, similar to previous studies [ 46 , 47 ]. Chemotherapy contributes to changes in taste such as altered structure of taste buds and number of taste cell receptors, and detection of drug sensation via saliva [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 90%
“…These findings suggest the necessity for nutritional intervention in these patients. Moreover, although one study found that toxicities were more common in advanced lung cancer patients with weight loss when receiving platinum-based chemotherapy 16 , we didn't find any significant difference in adverse events between two groups in this analysis, which may be because the toxicities of EGFR-TKI were slight and all population could be well tolerated.…”
Section: Discussionmentioning
confidence: 62%
“…In the present study, CLF resulted in a body weight reduction of 19% and vitamin C supplementation did not attenuate weight loss induced by cyclophosphamide. However, weight loss was more gradual than the acute effect observed in the group that did not receive vitamin C. This significant weight loss may have occurred due to the side effects of the drug (e.g., diarrhea, nausea, and/ or inappetence) as well the immunosuppressive state that may result in reduced feed intake and body weight loss as observed in humans 40 , but these side effects were not evaluated in this study.…”
Section: Discussionmentioning
confidence: 82%